Analisis Kinerja Aparatur Gampong dalam Pengelolaan Dana Desa (Studi pada Gampong di Kecamatan Kuta Blang Kabupaten Bireuen) - Iskandar, Iskandar; Endang, Syahriani (Aceh Cooperative Care, 2024)
The performance of village apparatus is questioned. This is natural, because they are increasingly required to be professional in facing the era of regional autonomy and transparency. The development of village progress is expected to lead to village independence, to achieve a decent living for village communities, and in turn not to continue to intend to migrate to the city. Therefore, this study aims to review the factors that cause the performance of village apparatus, especially in managing village funds. With a case study in a village in Kuta Blang District, Bireuen Regency. The study was limited to compensation, competence and motivation factors. An associative method was applied with a quantitative approach. The sample in this study was 180 village apparatus in managing village funds. The results are known, 1) The performance of the performance of village apparatus in Village Fund Management, each has an influence from the compensation aspect of 40.02%, the competence aspect of 39.41% and the work motivation aspect of 31.57%. 2) Simultaneously, compensation, competence and motivation have an effect on the performance of village apparatus in Village Fund Management in Kuta Blang District, Bireuen Regency by 50.8%.